Enhanced CO2 adsorption capacity and stability using CaO‐based adsorbents treated by hydration. Issue 10 (16th May 2013) - Wang, Shengping; Shen, Hui; Fan, Shasha; Zhao, Yujun; Ma, Xinbin; Gong, Jinlong
<x xml:space="preserve">Abstract</x> The synthesis of highly efficient CaO‐based sorbents using Ca(Ac)2 as a precursor and ethanol as a modification agent for CO2 capture is described. This adsorbent has several characteristics such as large surface area and pore volume and small particle size. The influence of ratio of ethanol and water on CO2 adsorption capacity was evaluated considering that the ethanol concentration could affect the pore structure of sorbents. The results showed that CaO modified by ethanol solution had a higher carbonization and better stability. Particularly, when the volume ratio of ethanol and water was 3, a performance of adsorption capacity of 74% and conversion of 94% was observed. CaO modified by ethanol solution had a superior performance due to the decrease of grain size and the formation of loose porous structure. The influence of steam on stability of adsorbents at high temperatures was examined, and it was found that with the existence of steam diffusion, the capacity of the sorbent could remain at a higher level and the stability was evidently improved. After 18 cycles of adsorption/desorption process, the capacity remained as high as 65%. It was proposed that dynamic and cyclic steam injection was favorable for preventing the sintering of sorbents and facilitating the diffusion of CO2. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3586–3593, 2013